Examining Entrepreneurial Intent of Kabul University Business School Students using The “TPB Model” and the Entrepreneurial Intention Questionnaire - Sedeqi, Ahmad Robin; Abdali, Sayed Mohammad Zarif; Qayomi, Maiwand (International Journal of Economics, Management and Accounting, 2024)
This study assesses the entrepreneurial intention of business school students, where Ajzen's Theory of Planned Behavior (TPB) is the primary conceptual model combined with data collection using the Liñán and Chen EIQ (Entrepreneurial Intention Questionnaire). Using convenience sampling, a total of 154 students from Kabul University, Afghanistan, were studied. We found that the EIQ psychometric properties were confirmed. Personal attitude, self-efficacy, and subjective norms were all predictors of entrepreneurship intent and thus verified in the study's regression analysis results. Because of the research design limitation, the findings cannot be generalized and may reveal different results over time or by the time students graduate. As one practical implication of the study, it is suggested that universities focus more on independent variables, such as personal attitude and self-efficacy, to build confidence in entrepreneurship among students. Future research can include moderator variables such as family influence, networking and communication, and Islamic values in supporting entrepreneurship intention. The psychometric properties of EIQ were confirmed.